Implementasi Bimbingan Kelompok Untuk Meningkatkan Empati Siswa - Marneva Nailul Amni Neva; Wahidah Fitriani (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
Aliyah (MA) Plus An Nahl Kabupaten Lima Puluh Kota through the Career Guidance Service. Based on the results of observations made by researchers before providing services in these classes there are still many students who do not have career plans. Based on the data obtained, the researcher conducted an action research that refers to career guidance service activities. The reason the researcher will provide career guidance service action is because the counseling teacher does not carry out the service and considers this service necessary to be provided to service participants. This activity is monitored using a checklist. From the results of the research carried out, there were several indicators that experienced an increase in the "very good" category, namely the indicator of introduction to the world of work with descriptors seeking information, the total percentage of 100% of 14 students, then Knowing how to choose a study program with a percentage of 93% of 13 students . And the indicator of knowing various types of secondary schools that can support careers has increased with a percentage of 93% of 13 students, and making decisions with a percentage of 93% of 13 students Keywords: Career guidance; career planing Â